2012
DOI: 10.26719/2012.18.10.1011
|View full text |Cite
|
Sign up to set email alerts
|

Physical and verbal/emotional abuse of schoolchildren, Lebanon, 2009

Abstract: The extent of physical and verbal/emotional abuse in schools in Lebanon is currently unknown. This cross-sectional study aimed to determine the prevalence and patterns of both forms of abuse among a nationally representative sample of Lebanese schoolchildren, aged 10-18 years, using a self-reported questionnaire. A total of 1177 schoolchildren, 49.6% females, median age 14 years, completed the survey; 76.4% and 81.2% of these had experienced physical and verbal/emotional abuse respectively at least once at sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
6
19
0
Order By: Relevance
“…Violence-related behaviour (being bullied, physically attacked and participation in a physical ght) decreased in this study, which concurs with four other studies [14,[24][25][26], while a few studies found an increase in one or more types of interpersonal violence, e.g., in Oman [16], the Philippines [15] and Venezuela [27]. In several older studies among adolescents in Lebanon, high rates of interpersonal violence have been reported [5][6][7], which compares with our high rates of interpersonal violence in the 2005 GSHS. It is possible that the high rates of interpersonal violence in 2005 were still related to the post-con ict situation in Lebanon, which subsequently subsided so that interpersonal violence decreased from 2005 to 2017.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Violence-related behaviour (being bullied, physically attacked and participation in a physical ght) decreased in this study, which concurs with four other studies [14,[24][25][26], while a few studies found an increase in one or more types of interpersonal violence, e.g., in Oman [16], the Philippines [15] and Venezuela [27]. In several older studies among adolescents in Lebanon, high rates of interpersonal violence have been reported [5][6][7], which compares with our high rates of interpersonal violence in the 2005 GSHS. It is possible that the high rates of interpersonal violence in 2005 were still related to the post-con ict situation in Lebanon, which subsequently subsided so that interpersonal violence decreased from 2005 to 2017.…”
Section: Discussionsupporting
confidence: 91%
“…In a national sample of adolescents in Lebanon in 2009, "76.4% and 81.2% of these had experienced physical and verbal/emotional abuse respectively at least once at school." [6], and in an investigation in 1028 Lebanese children (8-17 years), "54% reported at least one incident of physical abuse over a 1-year period" [7], and 30% were involved in bullying [8].…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5 This experience of violence was also common among school pupils in South Africa and Lebanon. [18][19][20] The high levels of violence in schools may be a reflection of the rising incidence of violence in the society as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies have found psychological violence to be commonest form of violence to students because its perpetration may be subtle and hidden from others. 9,18 Some students had experienced the different types of violence concurrently. Researchers have observed that physical violence is often accompanied by psychological abuse, and in one third to over one half of cases by sexual abuse as well.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of interpersonal violence, a high prevalence of involvement in physical fight (almost 42%) were found among school adolescents in Beirut, Lebanon [ 10 ]. In a national sample of adolescents in Lebanon in 2009, 76.4% had experienced physical abuse at school [ 11 ], and in a study in 8- to 17-year-old Lebanese children, 54% reported past year physical abuse [ 12 ], and 30% were involved in bullying [ 13 ]. In a household survey in 2015 in Lebanon, 57% of Lebanese and 65% of Syrian children had been exposed to some type of violent discipline [ 2 ].…”
Section: Introductionmentioning
confidence: 99%